2018
DOI: 10.3762/bjnano.9.121
|View full text |Cite
|
Sign up to set email alerts
|

Formation and development of nanometer-sized cybotactic clusters in bent-core nematic liquid crystalline compounds

Abstract: Two homologue achiral bent-core liquid crystals (LCs), BCN66 and BCN84, in their nematic phases are studied by dielectric spectroscopy in the frequency range 10 Hz–10 MHz. In each of these compounds, two relaxation processes are identified and assigned to (i) collective dynamics of molecules in nanometer-sized cybotactic clusters and (ii) individual molecular relaxations, in the ascending order of frequency of the probe field. The temperature and the bias electric field dependence of the dielectric strength an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 62 publications
3
12
0
Order By: Relevance
“…Several recent observations suggest the possibility of chiral superlayer ordering in achiral bent-core mesogens: Takanishi et al have identified such a structure in a SmCP phase of a bent-core mesogen doped with a chi-ral, rod-shaped molecule that as a neat material exhibits SmC * α and ferrielectric phases [20]; Abberley et al have reported a superlayer helix in a smectic phase of bent dimers of molecular rods [21]; Panarin and co-workers have recently proposed, based on AFM evidence, the existence of tilted, helical supermolecular ordering in several achiral bent-core mesogens with 4-cyanoresorcinol bisbenzoate cores [22]. Earlier investigations of this molecular family had concluded, however, that their polar phases were orthogonal, i.e., untilted and therefore not chiral [23,24].…”
mentioning
confidence: 99%
“…Several recent observations suggest the possibility of chiral superlayer ordering in achiral bent-core mesogens: Takanishi et al have identified such a structure in a SmCP phase of a bent-core mesogen doped with a chi-ral, rod-shaped molecule that as a neat material exhibits SmC * α and ferrielectric phases [20]; Abberley et al have reported a superlayer helix in a smectic phase of bent dimers of molecular rods [21]; Panarin and co-workers have recently proposed, based on AFM evidence, the existence of tilted, helical supermolecular ordering in several achiral bent-core mesogens with 4-cyanoresorcinol bisbenzoate cores [22]. Earlier investigations of this molecular family had concluded, however, that their polar phases were orthogonal, i.e., untilted and therefore not chiral [23,24].…”
mentioning
confidence: 99%
“…These clusters only occupy a fraction of the volume, and not all molecules form these clusters [34,35]. Experiments show that the clusters can also exist in the isotropic phase, and their size does not change significantly across the I-N transition -a unique property of BLCs that warrants further investigation [12,35,36,48,49]. As reported in [36], through detailed small-angle X-ray scattering (SAXS) and dielectric measurements, the N phase of the pristine LC 14-2M-CH 3 is cybotactic in nature, i.e., it contains smectic-like cybotactic clusters.…”
Section: Dielectric Studiesmentioning
confidence: 99%
“…The incorporation of QDs causes fR1 to shift to higher frequencies (∼ 220 Hz to ∼ 430 Hz). It indicates that there is an apparent reduction in size of the smectic-like cybotactic clusters [48]. This reduction can be estimated qualitatively by taking the ratio of the relaxation frequency fR1, for the pristine LC and its doped counterpart.…”
Section: Dielectric Studiesmentioning
confidence: 99%
“…Although one can consider the smectic clusters as long-living fluctuations of the smectic order, their persistence over broad temperature range suggest that they are more complex than merely a pretransitional effect. [20,[24][25][26] A combination of the ferroelectric LC order of bent-core mesogens and the photoswitchable nature of the azobenzene units has a great potential for the development of new multifunctional materials in which the polar response can be modulated with light. For this reason, azobenzene-based BCLCs attracted the attention of many researchers in recent years.…”
Section: Introductionmentioning
confidence: 99%
“…The model of the cybotactic N phase assumes the existence of smectic‐like nanosized clusters exhibiting a layered supramolecular structure (typically skewed) with intrinsic biaxial orientational order within the nematic phase (designated N CybC ). Although one can consider the smectic clusters as long‐living fluctuations of the smectic order, their persistence over broad temperature range suggest that they are more complex than merely a pretransitional effect [20,24–26] …”
Section: Introductionmentioning
confidence: 99%